Effects of various binding agents on the water stability of diets of Cirrhinus mrigala(Ham.) - Moond, R K; Sharma, O P; Jain, H K (Indian Journal of Fisheries, 2011)
Effects of various binding agents on the water stability of diets of Cirrhinus mrigala(Ham.)